ROSUS 2023 - Računalniška obdelava slik in njena uporaba v Sloveniji 2023: Zbornik 17. strokovne konference (University of Maribor Press, 2023)
ROSUS 2023: Computer image processing and its application in Slovenia 2023: Proceedings of the 17th Professional Conference. ROSUS 2023 – Computer image processing and its application in Slovenia 2022 is a professional conference that, since 2006, has been organised every year by the Institute of Computer Science of the Faculty of Electrical Engineering and Computer Science, University of Maribor. The conference connects researchers in the fields of Image Processing and Machine Vision with users of this knowledge, whereby users are coming from diverse industrial environments, such as Biomedicine, Sport, Entertainment, and related fields. The proceedings of ROSUS 2023 combine scientific articles by dozens of authors, including two invited lectures and several demonstration articles. Contributions represent the latest achievements of Slovenian experts in the fields of Image Processing and Vision, and also highlight trends and novelties in these areas. Great emphasis is on promotion of the economic usefulness of Image Processing and Vision applications in the Slovenian region. Namely, such software, due to high precision, robustness, and exceptional speed in information processing, provides new opportunities for penetration on the high technologies market.